Translation Techniques In The First Arabic Version Of Thirukkural: An Analysis Of Kokan's Methodology - K M A Ahamed Zubair (Jurnal Bahasa Arab, 2025)
Professor Mohammed Yousuf Kokan’s “Al-Abyath Al-Muqaddasa” significantly contributes to the field of translation and intercultural communication through his Arabic translation of the Thirukkural, a classical Tamil text. The main objective of this research article is to analyze Kokan’s translation methodology, highlighting how he conveys the philosophical and ethical message of Valluvar while ensuring cultural resonance with the Arabic-speaking audience. The methods used are textual analysis and translation. The results show that the Thirukkural, revered for its universal wisdom, serves as an ideal text for translation, embodying values ​​that transcend cultural boundaries. Kokan’s efforts have enriched Arabic literature and fostered a deeper understanding and appreciation of Tamil thought in the Arab world. This article provides an in-depth perspective on Kokan’s translation approach, which has built a bridge between Tamil and Arabic cultures.